1990
DOI: 10.1095/biolreprod43.5.885
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Concentration and Size of Testicular Macrophages during Development

Abstract: Structural and functional interactions exist between Leydig cells and testicular macrophages of adult rats. Since the function of Leydig cells changes during critical periods of development and postnatal maturation, it is possible that macrophages are in part involved in regulating this process. As a first step towards gaining an understanding of the development of this paracrine phenomenon, I have undertaken a series of studies designed to determine when macrophages first become identifiable in the fetal test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 11 publications
4
39
1
Order By: Relevance
“…Although macrophages are known to populate the interstitium of the postnatal and adult rat testis (20,47), little is known about their fetal origins. Although some reports have documented the presence of macrophages in the fetal rat testis as early as E16.5-E19 (47,48), there has been no investigation of the role of macrophages during the initial steps of fetal testis organogenesis. Here we demonstrated that differentiated macrophages expressing wellcharacterized markers such as F4/80 and IBA1 are detectable in the UGR at the initial stages of gonad specification (E10.5).…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophages are known to populate the interstitium of the postnatal and adult rat testis (20,47), little is known about their fetal origins. Although some reports have documented the presence of macrophages in the fetal rat testis as early as E16.5-E19 (47,48), there has been no investigation of the role of macrophages during the initial steps of fetal testis organogenesis. Here we demonstrated that differentiated macrophages expressing wellcharacterized markers such as F4/80 and IBA1 are detectable in the UGR at the initial stages of gonad specification (E10.5).…”
Section: Discussionmentioning
confidence: 99%
“…Control procedures concerning the specificity of bismuth staining were applied as recommended and the procedures for ED-2 IHC were as described by Hutson (1990). All sections were counterstained with toluidine blue.…”
Section: Methodsmentioning
confidence: 99%
“…It was therefore suggested that bismuth had accumulated in rat Leydig cells, exhibiting a direct toxic effect on these cells. Because macrophages are found in the testis at a relatively high concentration (Miller et al 1983;Hutson 1990) and have been shown to phagocytose a variety of foreign substances (Wei et al 1988), we were interested in determining if these cells also accumulate bismuth. Because testicular macrophages exert local influences on Leydig cells, accumulation of bismuth in these cells could have functional significance (Hutson 1994(Hutson ,1998.…”
mentioning
confidence: 99%
“…They are known to play important protective and functional roles during reproductive life (Hutson 2006;Pé rez et al 2013). When they first populate the testis is not clear: In rats, testicular macrophages were first reported to arise just before 19 dpc (Hutson 1990), but a subsequent study reported their presence ;3 d earlier (Livera et al 2006). It is commonly assumed that they arise from circulating blood monocytes (Hutson 2006).…”
Section: Macrophagesmentioning
confidence: 99%
“…Testicular macrophages have a distinctive phenotype, associating with Leydig cells to form junctional complexes (Christensen and Gillim 1969;Miller et al 1983;Hutson 1990). In the mature testis, macrophages influence steroidogenesis in Leydig cells, secreting 25-hydroxycholesterol, which is acquired by ALCs and used in testosterone synthesis (Lukyanenko et al , 2001Nes et al 2000).…”
Section: Macrophagesmentioning
confidence: 99%